2019
DOI: 10.1103/physrevd.100.054015
|View full text |Cite
|
Sign up to set email alerts
|

Solution to the Balitsky-Kovchegov equation with the collinearly improved kernel including impact-parameter dependence

Abstract: The solution to the impact-parameter dependent Balitsky-Kovchegov equation with the collinearly improved kernel is studied in detail. The solution does not present the phenomenon of Coulomb tails at large impact parameters that have affected previous studies. The origin of this behaviour is explored numerically. It is found to be linked to the fact that this kernel suppresses large daughter dipoles. Solutions based on a physics motivated form of the initial condition are used to compute predictions for structu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 79 publications
0
59
0
Order By: Relevance
“…To conclude, we can see from the above discussion that the prescription of the QCD running coupling has a strong impact on the rapidity dependence of the S-matrix. The SDRC prescription takes a dramatic suppression on the evolution speed of the dipole scattering amplitude, which is favored by HERA data [18,35] and satisfies the theoretical expectations [21].…”
Section: Collinearly Improved Balitsky-kovchegov Equation and Its mentioning
confidence: 80%
See 3 more Smart Citations
“…To conclude, we can see from the above discussion that the prescription of the QCD running coupling has a strong impact on the rapidity dependence of the S-matrix. The SDRC prescription takes a dramatic suppression on the evolution speed of the dipole scattering amplitude, which is favored by HERA data [18,35] and satisfies the theoretical expectations [21].…”
Section: Collinearly Improved Balitsky-kovchegov Equation and Its mentioning
confidence: 80%
“…However, the recent studies in Refs. [17,18,35] found that the evolution equation with the SDRC prescription has been advocated to be the correct QCD running coupling prescription, since it is favored by the HERA data at a phenomenological level. It was also pointed out in Ref.…”
Section: Solutions To the Evolution Equations With The Smallest mentioning
confidence: 99%
See 2 more Smart Citations
“…At first sight the recent papers [25,26] have questioned the need of a new dimensional scale, since they demonstrate that the next-to-leading order BFKL equation generates the exponential type of the impact parameter behavior without the need of a new dimensional scale. However, it turns out [27] that the NLO corrections do not change the powerlike decrease of the scattering amplitude at large impact parameter, generating the exponential-type decreases in the large but limited region of the values of the impact parameter.…”
Section: Introductionmentioning
confidence: 99%